Thursday

April 24, 2014

April 24, 2014

Posted by **shelly** on Tuesday, June 23, 2009 at 10:57am.

- college math -
**MathMate**, Tuesday, June 23, 2009 at 11:06amExpand (remove parentheses) and collect terms in decreasing powers of a:

(-8a^2+4a+2) = -8a^2+4a+2

-(8a+2) = -8a-2

Since the subtraction is implied in the negation of the secnd expression, you only have to**add**the two resulting expressions and regroup in decreasing powers of a.

Post your results if you need confirmation of the answer or additional help.

**Related Questions**

math - (4a^3 - 7a^2) - (8a^3 + 1a^2) Subtract = 4a^3 - 7a^2-8a^3 - 1a^3 = 4a^3...

Math - Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B...

math - 5/8a+6=3/4a 6=1/8a a=6/8 is this correct? thank you.

math - 8a+2b=2 -8a+b=13 3b = 15 b = 5 8a + 10 = 2 8a = -8 a = -1 How do I write ...

algebra 1 - 7a+[4a-6b-(8a+2b)] ok so you would get this 7a+[4a-6b-8a-2b]<--- ...

Calculus; Limits - Evaluate limit, x -> a, [(x + 4a)^2 - 25a^2] / [x - a] My ...

8th math(Algebra) - what is 8a+b=1 8a-3b=3

Math - solve the elimination method 8a+2b=2 -8a+b=13 determined the solution of ...

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

math - find the value of a^3-1/8a^3 ,if a^2+1/4a^2=10